Sistema híbrido de armazenamento de energia integrado a um conversor bidirecional de interface usado para suavizar intermitências entre uma microrrede ca Trifásica e a rede elétrica monofásica - Pelz, Guilherme Masquetti (2023)
This thesis presents a Hybrid Energy Storage System (HESS) integrated to a Bidirectional Grid Interface Converter (BGIC) that operates between the single-phase power supply and the threephase AC microgrid, which is used to smooth the transfer of the power intermittencies from the microgrid to the electrical power system. Thus, the HESS absorbs/supplies the difference between the power of the grid and the microgrid, in the seconds following the power variations of the microgrid, preventing such variations from behaving as disturbances to the electrical system. On the other hand, after the establishment of the steady state, in which the grid supplies the demand of the microgrid, there is no energy circulation through the HESS. The complete system consists of a Unified Power Quality Conditioner (UPQC) coupled, through an isolated bidirectional DC-DC converter called Dual-Active-Bridge (DAB), to the Hybrid Energy Storage System comprised of batteries and ultracapacitors. The UPQC is connected between the single-phase grid and the three-phase four-wire microgrid, in which the connection of single-phase and three-phase loads is planned, in addition to distributed single-phase and threephase generators. Thus, in addition to controlling the power flow between the grid and the microgrid, this converter ensures low total harmonic distortion of the grid current and unity power factor, and supplies balanced, regulated three-phase voltages with low total harmonic distortion to the loads and distributed generators connected to the microgrid. Additional contributions related to the dimensioning of the HESS battery/ultracapacitor and related to the voltage and current controllers of the converters involved are also presented, such as a methodology for designing resonant controllers using the differential evolution optimization method, as well as the filtering of oscillatory components of the system's DC-link, preventing the propagation of these components to both the AC microgrid and the HESS. The verification of the theoretical results and the performance analysis of the proposed system is achieved through experimental results obtained by a prototype developed in the laboratory.